2018
DOI: 10.1186/s12889-018-6125-y
|View full text |Cite
|
Sign up to set email alerts
|

Work-related musculoskeletal problems related to laboratory training in university medical science students: a cross sectional survey

Abstract: BackgroundWork-related musculoskeletal problems impact everyday function, working ability, and quality of life. Unaddressed musculoskeletal problems can lead to major injury and loss of function, contributing to participation restrictions, economic loss and the increasing burden of disease worldwide. Medical science laboratory technicians are not immune with reported work-related musculoskeletal problems between 40 and 80%. Similar data is not available for medical science students, who may be the most vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…Consistent with literature [ 51 ], working posture (bending and/or twisting) has been identified as a considerable risk factor for neck and shoulder pains in the current investigation. A continuous deviation from normal/recommended working positions (usually neutral)/ could adversely affect neck and shoulder [ 52 ]. There have been wide documents which support the significant relations of working in prolonged sitting positions and the likelihood of developing neck and shoulder impairments [ 53 – 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with literature [ 51 ], working posture (bending and/or twisting) has been identified as a considerable risk factor for neck and shoulder pains in the current investigation. A continuous deviation from normal/recommended working positions (usually neutral)/ could adversely affect neck and shoulder [ 52 ]. There have been wide documents which support the significant relations of working in prolonged sitting positions and the likelihood of developing neck and shoulder impairments [ 53 – 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…People often assume that medical science education provides greater knowledge to students to keep them healthy and fit. In recent years, great effort has been given on the well-being and the quality of life to patients and other populations [2,3] but few studies have assessed the well-being of young medical science professionals [4,5]. At the early stage of their careers, new medical science students are more vulnerable to adopt unhealth lifestyle, which may be due to the challenge of living independently without parental constraints, changing eating behaviour, high academic demands with longer sedentary period at lectures and computer-screen and managing an active social life in the meantime [4].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the impact of unhealthy lifestyle components on cardiorespiratory fitness (CRF) and heart rate recovery of new medical science students is an important step to keep this young generation healthy. However, few studies had examined the health of medical science students relied on self-reported data [4,5]. Little information is available based on objective physical activity measures and the association between these measures and the lifestyle components for these early career health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Widanarko and colleagues surveyed several occupational/industrial groups and noted that 92% of office workers have reported musculoskeletal disorder symptoms [20]. In another study, about 63% of office workers pinpointed work as the major contributors to their musculoskeletal problems [21]. A similar study at a nearby tertiary hospital in our study area noted that the workers in their study were properly oriented about work ergonomics, but exhibited poor practice thereby placing them at increased risk for developing musculoskeletal disorder symptoms [22].…”
Section: Discussionmentioning
confidence: 57%